On the number of cut-vertices in a graph - Glenn Hopkins; William Staton (International Journal of Mathematics and Mathematical Sciences)
A connected graph with n vertices contains no more than r2r-2(n-2) cutvertices of degree r. All graphs in which the bound is achieved are described. In addition, for graphs of maximum degree three and minimum δ, best possible bounds are obtained for δ=1, 2, 3.